2014
DOI: 10.1152/ajpregu.00131.2014
|View full text |Cite
|
Sign up to set email alerts
|

Shp2 signaling in POMC neurons is important for leptin's actions on blood pressure, energy balance, and glucose regulation

Abstract: Previous studies showed that Src homology-2 tyrosine phosphatase (Shp2) is an important regulator of body weight. In this study, we examined the impact of Shp2 deficiency specifically in proopiomelanocortin (POMC) neurons on metabolic and cardiovascular function and on chronic blood pressure (BP) and metabolic responses to leptin. Mice with Shp2 deleted in POMC neurons (Shp2/Pomc-cre) and control mice (Shp2(flox/flox)) were implanted with telemetry probes and venous catheters for measurement of mean arterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…Thus, the ERK1/2 pathway appears to be more important for metabolic processes such as thermogenesis, as opposed to leptin’s cardiovascular sympathetic effects. However, deletion of the protein tyrosine phosphatase Shp2 which is upstream to the ERK1/2 signaling from the forebrain or POMC neurons not only prevented the anorectic effects of leptin but also attenuated its pressor effect [64, 65]. While Shp2 regulates a number of intracellular processes with respect to leptin signaling it is generally recognized as a critical component of the ERK1/2 pathway, indicating that ERK1/2 may not exclusively regulate the metabolic effects of leptin.…”
Section: Molecular Pathways Underlying Leptin Actionmentioning
confidence: 99%
“…Thus, the ERK1/2 pathway appears to be more important for metabolic processes such as thermogenesis, as opposed to leptin’s cardiovascular sympathetic effects. However, deletion of the protein tyrosine phosphatase Shp2 which is upstream to the ERK1/2 signaling from the forebrain or POMC neurons not only prevented the anorectic effects of leptin but also attenuated its pressor effect [64, 65]. While Shp2 regulates a number of intracellular processes with respect to leptin signaling it is generally recognized as a critical component of the ERK1/2 pathway, indicating that ERK1/2 may not exclusively regulate the metabolic effects of leptin.…”
Section: Molecular Pathways Underlying Leptin Actionmentioning
confidence: 99%
“…SHP2 deletion in forebrain neurons also attenuated leptin’s ability to reduce food intake and raise BP [72]. We also found that SHP2 signaling in POMC neurons contributes to the chronic BP and glucose-lowering effects of leptin but plays only a modest role in body weight regulation [73••], suggesting that SHP2 in POMC neurons may also contribute to the effects of leptin on SNS activity and BP. IRS2-PI3K signaling may also mediate leptin’s effect on SNS activity and BP.…”
Section: Selective Leptin Resistance In Obesity: Neuronal-specific Acmentioning
confidence: 90%
“…Ces effets identifiés in vitro ont été confirmés in vivo, la perte d'expression de SHP2 au niveau neuronal chez la souris conduisant à une hyper-activation de la voie JAK2/STAT3 et à une hypoactivation de Erk1/2 en réponse à la leptine dans l'hypothalamus [30]. Le lien entre SHP2 et l'action anorexigène de la leptine a été renforcé in vivo, la délétion de SHP2 au niveau neuronal dans plusieurs modèles murins conduisant à une hyperphagie associée à une obésité, un diabète et une résis-tance à la leptine, par des mécanismes moléculaires encore mal compris [31,32].…”
Section: Shp2 Et Balance éNergétiqueunclassified